Designing A Training Information System at Seameo Qitep in Science Using PHP Laravel - Yadi, Depras Nur; Saefuloh, Suganda; Syahidin, Yuda (Journal of Information System, Informatics and Computing; Vol 6 No 1 (2022): JISICOM: June 2022, 2022)
Information system technology that is growing rapidly every year makes several aspects of life very dependent on technology. The ease and effectiveness and efficiency of technology make the information system spread quickly in various circles as well as professions, not a few companies or organizations that have hybridized or combined manual and technology, including the implementation of learning and training in the context of development or what is often known as technology. training center. Currently the SEAMEO QITEP In Science training center is trying to do a hybrid training, so this research is aimed at designing a training information system at SEAMEO QITEP In Science. This design will be made using the UML (United Modeling Language) method, which is a capital oriented the object will also use the PHP programming language (PHP: Hypertext Pre-processor) with the laravel framework, and use MYSQL as the database. The Waterfall method was chosen as the development method, this research will produce a web-based SEAMEO QITEP In Science education and training information system in which it can make it easier for training participants as well as training administration administrators to be more practical and effective.